THE IMPACT OF TEACHERS AND SEVERAL PSYCHOLOGICAL FACTORS ON THE COVERAGE OF SPEECH BARRIERS - Lola Eshankulova (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article aims to analyze the importance of teachers` role and different types of methods for illumination of psychological issues faced by students in speaking and learning English language. Speaking is the most fundamental skill by which people express their thoughts. Communication is the backbone of our society. Without communication skills, the ability to progress in the contemporary world and in life, itself, would be nearly impossible. Thus, it is vital for teachers to examine even minor problems in speaking so that they can seek for appropriate solutions to them. This preliminary study collected data about challenges in speaking such as lack of confidence, shyness, fear of making mistakes when speaking the English language, lack of motivation in students in speaking the English language or nervous in speaking the English language in public. The finding depicts that most of the vicissitudes are strongly related to psychology, in this paper will be discussed a great number of approaches to overcome speech barriers.